Selective Formation of Epoxylimonene Catalyzed by Phosphonyl/Arsoníyl Derivatives of Trivacant Polyoxotungstates at Low Temperature. Issue 7 (12th February 2020) - Makrygenni, Ourania; Vanmairis, Louise; Taourit, Sabrina; Launay, Franck; Shum Cheong Sing, Alain; Proust, Anna; Gérard, Hélène; Villanneau, Richard
Abstract: Invited for the cover of this issue are Richard Villanneau, Sorbonne Université, Paris, Alain ShumàCheongàSing, Université de la Réunion, Saint‐Denis, France, and co‐workers. The cover image shows the oxidation of limonene to epoxylimonene against a background of orange trees typical of Réunion Island. Abstract : This class of catalysts may thus be considered as ideal candidates for the scale‐up of the selective oxidation of terpenes to a practical biorefinery, that is, a facility that processes agricultural material to commercially useful chemicals … Read more about the story behind the cover in the Cover Profile and about the research itself in the Full Paper by A. Shum Cheong Sing, R. Villanneau et al.